A Time Series Analysis of the Effect of Internal Audit Activities on External Audit Fees (Book). - Hendrickson, Harvey S.; Williams, David D. (The Accounting Review, 1986)
Reviews the book "A Time Series Analysis of the Effect of Internal Audit Activities on External Audit Fees," by Wanda A. Wallace.